2010
DOI: 10.1007/s12402-010-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: differential effects of methylphenidate-OROS on working memory and attention functions in children with attention-deficit/hyperactivity disorder with and without behavioural comorbidities

Abstract: To examine the effects of methylphenidate-OROS (MPH-OROS) on working memory (WM) and attention functions in children with attention-deficit hyperactivity disorder (ADHD), and to investigate whether there is a differential effect in ADHD children with (ADHD+) and without (ADHD-) behavioural comorbidities. Participants included a clinic referred sample of 12 stimulant naïve school-aged children with a diagnosis of combined ADHD according to the DSM-IV criteria (6 ADHD+, 6 ADHD-), and 11 healthy children. A neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Converging lines of evidence suggest that pure ADHD and comorbid forms of ADHD differ in treatment response and possibly in neural endophenotypes [Jensen et al, 2001;Newcorn et al, 2001;Rubio et al, 2011;Sauder et al, 2012;Takeda et al, 2012]. By differentiating ADHD subgroups based on comorbidity and utilizing comprehensive DKI-based diffusion metrics to assess tissue microstructure, we were able to detect distinct atypical agerelated patterns of tissue microstructural complexity within the ADHD-pure subgroup, which were obscured when youth with ADHD and comorbid disorders were included in analyses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Converging lines of evidence suggest that pure ADHD and comorbid forms of ADHD differ in treatment response and possibly in neural endophenotypes [Jensen et al, 2001;Newcorn et al, 2001;Rubio et al, 2011;Sauder et al, 2012;Takeda et al, 2012]. By differentiating ADHD subgroups based on comorbidity and utilizing comprehensive DKI-based diffusion metrics to assess tissue microstructure, we were able to detect distinct atypical agerelated patterns of tissue microstructural complexity within the ADHD-pure subgroup, which were obscured when youth with ADHD and comorbid disorders were included in analyses.…”
Section: Discussionmentioning
confidence: 89%
“…More than 66% of attention‐deficit/hyperactivity disorder (ADHD) cases have diverse comorbid disorders including externalizing (e.g., oppositional defiant and conduct disorders) and internalizing disorders (e.g., anxiety and mood disorders). Different comorbid forms of ADHD and pure ADHD have been associated with distinct core symptoms, clinical outcomes, and treatment responses [Jensen et al, ; Newcorn et al, ; Rubio et al, ; Takeda et al, ]. Although the existence of distinct clinical phenotypes suggests potentially differential neural endophenotypes, most neuroimaging studies have included heterogeneous samples without specifically accounting for comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Although this dose might be insufficient to induce effects on behaviour in some patients, this does not imply lack of neural effects, as we have seen normalization effects in terms of functional connectivity. Moreover, neuropsychological studies have shown that effects of long-term administration were more profound than acute effect of MPH, especially in participants with significant impaired working memory (Hammerness et al, 2014; Kubas et al, 2012; Rubio et al, 2011; Schweren et al, 2013).…”
Section: Discussionmentioning
confidence: 99%